Engagement of Generation Z in Company-Customer Relationships on Social Media – A Comparative Analysis of Poland and Great Britain - Olga Ławińska; Anna Korombel (Tržište)
Purpose – This article aims to identify the types of social media activities that Generation Z expects from companies. Design/Methodology/Approach – Empirical research was conducted in 2023 among students in Poland and Great Britain using a structured survey based on the CATI (Computer-Assisted Telephone Interviewing) method. Descriptive statistical tools were applied to analyse the collected data. Findings and Implications – The study identified key social media activities expected by Generation Z and revealed correlations between these expectations and the respondents’ gender and place of residence. The insights gained can help social media managers align their communication strategies with Generation Z’s preferences, thereby enhancing customer engagement. Limitations – The study’s limitations stem from the nature of survey research, including the potential for superficial understanding of the topic and the risk of inaccurate responses. Moreover, the relatively small sample size limits the generalizability of the findings. Originality – This paper addresses professionals responsible for managing interactions with Generation Z on social media platforms. The findings expand the existing body of knowledge by highlighting how gender, place of residence, and nationality influence the online engagement of Generation Z.